Diffusion bonding of RAFM steels: evolution of interfacial oxide layer with pressure and microstructure and mechanical property after post bonding heat treatment - Chen, Jianguo; Wang, Wanjun; Dong, Ji; Wang, Chuancai; Wei, Yushun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
The effect of elevating the bonding pressure from 10 to 20 MPa (5 MPa interval) at 1050 oC for 60 minutes on the diffusion bonded joint of reduced activation ferritic/martensitic (RAFM) steel was studied. The results indicate that as the bonding pressure increases, the joint quality correspondingly improves. The oxide layer at the bonding interface underwent an evolution process from continuous to discontinuous and ultimately disappeared with the increase of bonding pressure. The optimal joint was achieved at the pressure of 20 MPa in this work. Considering the exploration of joint reliability in engineering applications, the optimal joint was subjected to a post bonding heat treatment (PBHT) of 750 oC for 90 minutes. The diffusion bonding sample subjected to PBHT displays microstructural characteristics and tensile properties similar to those of the base metal. Notably, tensile fracture does not occur at the bonding interface, but in the base metal far from the interface.